The Effect of Communication and Work Spirit on the Effectiveness of Employee Performance at Work Training Center in Seluma Regency - Ariyando Ariyando; Neri Susanti; Meiffa Heriyanti (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2021)
This study was aimed to determine the effect of communication and spirit on the effectiveness of employee performance at Job Training Center in Seluma Regency. The sample of this study was 38 employees at Job Training Center in Seluma Regency. The data was collected by using a questionnaire and then analyzed by using multiple linear regression, determination test and hypothesis testing. The results showed a positive regression direction, Y = 0.973 + 0.370X1 + 0.625X2. It showed that there is a positive influence between X1 (communication) and X2 (work spirit) on work effectiveness (Y). Means that if the variables of communication and morale increase, it will increase work effectiveness. The value of the coefficient of determination is 0.595. This means that X1 (communication) and X2 (work spirit) affect the effectiveness of work performance (Y) by 59.5% while the remaining 40.5% is influenced by other variables not examined in this study. The results of the t-test at a significance level of 0.05 explained that partially the communication and work spirit variables had a significant influence on the effectiveness of employees work performances at Job Training Center in Seluma Regency. Moreover, the F test results at a significance level of 0.05 explained that the communication and work spirit variables has a significant simultaneous effect on effectiveness of employees work performance at Job Training Center in Seluma Regency.